Lighting, sleep and circadian rhythm: An intervention study in the intensive care unit. Issue 6 (December 2015) - Engwall, Marie; Fridh, Isabell; Johansson, Lotta; Bergbom, Ingegerd; Lindahl, Berit
Summary: Patients in an intensive care unit (ICU) may risk disruption of their circadian rhythm. In an intervention research project a cycled lighting system was set up in an ICU room to support patients' circadian rhythm. Part I aimed to compare experiences of the lighting environment in two rooms with different lighting environments by lighting experiences questionnaire. The results indicated differences in advantage for the patients in the intervention room ( n = 48), in perception of daytime brightness ( p = 0.004). In nighttime, greater lighting variation ( p = 0.005) was found in the ordinary room ( n = 52). Part II aimed to describe experiences of lighting in the room equipped with the cycled lighting environment. Patients ( n = 19) were interviewed and the results were presented in categories: "A dynamic lighting environment", "Impact of lighting on patients' sleep", "The impact of lighting/lights on circadian rhythm" and "The lighting calms". Most had experiences from sleep disorders and half had nightmares/sights and circadian rhythm disruption. Nearly all were pleased with the cycled lighting environment, which together with daylight supported their circadian rhythm. In night's actual lighting levels helped patients and staff to connect which engendered feelings of calm.